DEVELOPMENT OF A PERIODIC ELEMENTARY SYSTEM MODULE FOR BOARDING SCHOOL STUDENTS IN IMPROVING VISUAL INTELLIGENCE - Khusna, Anggia Ulfia; Janah, Shafna Nor; Halwi, Adam Al; Dwiningsih, Kusumawati (JCER (Journal of Chemistry Education Research), 2024)
The periodic system of elements is one of the complex chemical materials. The results of previous research show that the learning achievement of boarding high school students has an understanding that is only limited to the macroscopic level. Visualization of chemical representation level requires high visual intelligence. Therefore, researchers developed a module of periodic system of elements as an independent learning media for high school boarding school students in improving visual intelligence. This study aims to analyze the validity, practicality, and effectiveness of the module. The type of research used is the ADDIE method with five stages, namely Analyze (analysis), Design (design), Develop (development), Implement (implementation), and Evaluate (evaluation). The module in terms of content and construction showed a very valid category. The results of observations of module implementation show a very practical category. The module is very effective to improve students' visual intelligence with an n-gain value of 0.753434. The results showed that the periodic system of elements module is feasible to use as a solution to improve students' visual intelligence.